Language acquisition by the deaf: An interdisciplinary study - Campos , Adriano Ricardo de; Lima , Cleusa Elias Brito de; Santos, Elzeny Wakemaker de Souza (Seven Editora, 2023)
This study brings the experience report of deaf students in elementary school in a municipal school in the city of Rubiataba/Goiás aiming to discuss the acquisition of language in the interdisciplinary process of teaching-learning of the deaf person. It also focuses on understanding deaf education as a Human Right of social action, highlighting the relevance of interdisciplinarity in deaf education and expose the main methods that guide the teaching of Libras in language acquisition. The study is supported by the current legal contributions and the works of Quadros (2007, 2008), as well as the contributions of Fazenda (1998), Strobel (2008) and Freire (1998). The results indicate the need to develop pedagogical strategies to stimulate the learning of the Deaf student in an interdisciplinary way, thus enhancing the formation of social and communicative autonomy of the active subject in cultural scenarios that make them become recognized and respected for their cultural identity. DOI:https://doi.org/10.56238/alookdevelopv1-014